Pengaruh Corporate Governance dan Pengungkapan Corporate Social Responsibility Terhadap Agresivitas Pajak - Rengganis, Maria Yulia dwi; Dwija Putri, I.G.A.M Asri (E-Jurnal Akuntansi, 2018)
The tax aggressiveness is step of company as strategy minimize the tax that must paid. This research uses ETR as proxy of the tax aggressiveness. The lower value of ETR of company depicts the high aggressiveness tax those companies. This research has a purpose to giving information about the impact of  Corporate Governance and Disclosure of Corporate Social Responsibility On the Aggressiveness Tax representative with ETR. All of manufacturing companies listed on Indonesian stocks Exchanges on 2013-2015 is the population of this research. Companies selected into the sample after deducting some of the criteria is as much  99 of the company observations. This study has results that prove the disclosure of CSR affect the ETR as proxy of tax aggressiveness. Value of CSR disclosure company high, so value of ETR is higher which describe the lower aggressiveness tax of the companies.
Keywords: Tax Aggressiveness, Corporate Governance, Corporate Social Responsibility